Quantitative methods used for understanding the taxonomy of acritarchs: a case study of the Middle Ordovician genus Frankea Burmann 1970. (22nd December 2017) - Wang, Wenhui; Monnet, Claude; Servais, Thomas
ABSTRACT: The triangular-shaped acritarch genus Frankea, which displays characteristically branched appendices, has considerable stratigraphical and palaeobiogeographical significance in the Ordovician. High intraspecific variability of terminal processes (appendices) numbers and process lengths within Frankea suggest that the genus could be suitable for use in studying the relationship between morphological characters and environmental conditions. Quantitative multivariate exploratory analyses on Frankea indicate that the length of the appendices varies according to different localities and is most probably ecologically dependent and not age diagnostic as previously suggested. Principal components analyses and discriminant analyses are used to assess the original specific classification of Frankea . The morphometric analyses suggest that usage of quantitative characters, such as the process length, should be taken into consideration during the separation of species. A comprehensive discussion of qualitative and quantitative characters is carried out and suggests there are only three species of Frankea: F. hamata, F. hamulata and F. sartbernardensis .